Kesan penggantian litium ke atas struktur, sifat fizikal dan sifat elektrik terhadap seramik BCZT - Haziqah Fadhlina,; A. Atiqah,; Zalita Zainuddin,; Nur Shakila Othman,; Solehah Ali,; Nor Amalina, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The invention of novel lead-free piezoelectric materials with ABO3 perovskite structure, based on barium calcium zirconate titanate (BCZT) for application in various device especially in sensor application. In this work, BCZT with lithium substitution at the calcium site with composition Ba0.85Ca0.15-xLi2xZr0.1Ti0.9O3 (x = 0.00, 0.03, 0.06, 0.09 and 0.12) were synthesized by using the conventional, solid state reaction method. The influence of different Li content on the structure, microstructure, density, and electrical properties were investigated. The results show that substitution led to the improvement of the physical and electrical properties of the piezoelectric ceramic materials. The physical properties show the largest grain size and the highest value of density, ρ which is 4.158 g/cm3 for x = 0.06. This physical properties led to the highest value of piezoelectric coefficient, d33, remnant polarisation, Pr and saturated polarization, Ps which are 304.6 pC/N, 3.27 µC/cm2 , and 5.54 µC/cm2 , respectively, while the highest dielectric constant, ɛr was 3994 when x = 0.12.